Low levels of vitamin D in population exposed to significant pollution - Josef Richter; Vaclav Vetvicka; Stanislava Richterova (临床与病理杂志, 2022)
Background: In recent years, monitoring of vitamin D levels and possible use of supplementation is gaining attention. Numerous studies showed low levels of vitamin D in winter months followed by improvement during summer. These changes are mostly dependent on the level of sun exposure, but also on geographical location, genetic factors, social-economic status, quality of nutrition and environmental pollution. In this observation we found significant decrease in vitamin D levels I populations exposed to extreme environmental pollution in area of central Europe. This region is known for extreme burden from microparticles originating in chemical industry, surface coal mining and cold-based power stations. Methods: Vitamin D levels in all patients was determined by ELISA. Results: Using 540 patients in our Department of clinical immunology and allergology we measured the levels of vitamin D in 2016 to 2021 period. In only 4 patients (0.74%) we found vitamin D levels higher than 30 ng/mL. The curve of observed values does not reflect dependency on sun exposure and does not change during the year. Conclusion: We discuss the effect of environmental contaminants, lifestyle and economic and social factors. From our observations, we propose to directly supplement population with vitamin D, particularly children and seniors.